Non-ergodic fragmentation upon collision-induced activation of cysteine-water cluster cations - Tiefenthaler, Lukas; Scheier, Paul; Erdmann, Ewa; Aguirre, Néstor F; Díaz-Tendero, Sergio; Luxford, Thomas F M; Kočišek, Jaroslav (Physical chemistry chemical physics, 2023)
Cysteine-water cluster cations Cys(H2O)3,6+ and Cys(H2O)3,6H+ are assembled in He droplets and probed by tandem mass spectrometry with collision-induced activation. Benchmark experimental data for this biologically important system are complemented with theory to elucidate the details of the collision-induced activation process. Experimental energy thresholds for successive release of water are compared to water dissociation energies from DFT calculations showing that clusters do not only fragment exclusively by sequential emission of single water molecules but also by the release of small water clusters. Release of clustered water is observed also in the ADMP (atom centered density matrix propagation) molecular dynamics model of small Cys(H2O)3+ and Cys(H2O)3H+ clusters. For large clusters Cys(H2O)6+ and Cys(H2O)6H+ the less computationally demanding statistical Microcanonical Metropolis Monte-Carlo method (M3C) is used to model the experimental fragmentation patterns. We are able to detail the energy redistribution in clusters upon collision activation. In the present case, about two thirds of the collision energy redistribute via an ergodic process, while the remaining one third is transferred into a non-ergodic channel leading to ejection of a single water molecule from the cluster. In contrast to molecular fragmentation, which can be well described by statistical models, modelling of collision-induced activation of weakly bound clusters requires inclusion of non-ergodic processes.